The Consumption Effect of Indigenous Probiotic Powder Lactobacillus plantarum Dad-13 on Gut Microbiota Population and Short Chain Fatty Acids in Students of SMPN 1 Pangururan, Samosir - Manurung, Nancy Eka Putri; Hasan, Pratama Nur; Juffrie, Mohammad; Utami, Tyas; Yanti, Rini; Rahayu, Endang Sutriswati (Indonesian Food and Nutrition Progress, 2024)
The human intestine is a diverse ecosystem populated by microbiota affected by several factors, including age. The aim of this research was to evaluate the effects of the probiotic powder Lactobacillus plantarum Dad-13 on the numbers of gut microbiota, short-chain fatty acids (SCFA), and fecal characteristics in healthy adolescents. This research was conducted at SMPN 1 Pangururan, Samosir, with a randomized, double-blind, parallel placebo-controlled trial. 54 healthy adolescents aged 13 to 14 were divided into two groups, one consumed a gram of skimmed milk powder (placebo group) and the other ingested powder containing L. plantarum Dad-13 with 1.18 × 109 CFU/gram (probiotic group). After 33 days of intervention, the height of placebo group (149.42 ± 5.03 cm) and probiotic group (154.37 ± 4.67 cm) increased significantly. Significant increases in body weight (44.35 kg ± 4.61 to 45.20 kg ± 4.78) and BMI (and 18.77 ± 2.12 to 18.99 ± 2.11) were observed in the probiotic group. In the probiotic group, the numbers of gut microbiota were not significantly affected (p > 0.05). The amount of SCFA and fecal characteristics of both groups showed no significant differences. Thus, the consumption of L. plantarum Dad-13 increased weight, height, and BMI but could not influence the numbers of gut microbiota, SCFA, and the fecal characteristics of healthy adolescents.